Effect and safety of extracorporeal shockwave therapy for postherpetic neuralgia: A randomized single-blind clinical study - Chen, Lu; Qing, Ailing; Zhu, Tao; Yang, Pingliang; Ye, Ling (Frontiers in Neurology, 2022)
Objective: To evaluate the efficacy and safety of extracorporeal shockwave therapy (ESWT) for postherpetic neuralgia. Design: Randomized single-blind clinical study. Patients: Patients with postherpetic neuralgia. Methods: Patients were randomly divided into control group and ESWT group. The control group received conventional treatment while the ESWT group received conventional treatment and ESWT. The primary outcome is pain degree assessed by numeric rating scales (NRS), the secondary outcomes include brief pain inventory (BPI), self-rating Anxiety Scale (SAS）, self-rating depression scale (SDS) and Pittsburgh sleep quality index (PSQI). Data was collected at baseline and weeks 1, 4, and 12. Linear mixed-effects models were applied to repeated measurement data. Results: NRS, BPI, SAS, SDS and PSQI scores decreased over time in both groups. NRS and SDS scores of ESWT group was statistically lower than control group. There was no time × group interaction in mixed model analysis. Baseline age was corelated with NRS score and BPI scores and invasive treatment was related to PSQI scores, with no interaction effect for baseline confounders observed. No adverse event was observed during the process of this trial. Conclusion: ESWT combined with conventional treatment could relief pain and improve psychological state in patients with postherpetic neuralgia without serious adverse effects.